#TITLE_ALTERNATIVE# - SHOFWAN HARUN (NIM: 22014323), IMAM
The WD field is a gas field with Paleocene and Middle Jurassic reservoirs located in the Bintuni basin. The depositional environment for the Jurassic reservoir is shallow marine, while the Paleocene reservoir depositional environment is deep water to shallow marine. Paleocene architectural elements include basin floor fans (submarine lobes), submarine channels, and shelf-edge delta systems. The WD field structure is a NW-SE elongated anticline, dissected by strike-slip faults that potentially create reservoir compartmentalization. The WD field development requires a clear understanding of the structural framework. Structural framework analysis in the WD field comprises interpretation of seismic data and its limitations, fault interpretation within the context of regional tectonics, depth conversion, and depth map analysis. Structural framework analysis, reservoir distribution and their relationship with potential reservoir compartmentalization is validated by reservoir pressure versus depth plots obtained from formation tests. The WD field has three main culminations, which are North-Central, South, and a pop-up structure near WD3 well. There are three fault trends in the field i.e.: W-E, NE-SW, and ENE-WSW. The Miocene aged W-E strike-slip trend is the key element controlling the structural framework and creates potential reservoir compartmentalization. These W-E strike-slip faults have vertikal offset up to 1000 ft (304.8 m) and were locally reactivated during the Pliocene-Pleistocene. The combination of structural, reservoir distribution model, and multiple hydrocarbon contact interpretations provides description of trap and compartmentalization Paleocene reservoir.